Optimal stress : - Scott, Carol (Wiley, 2010)
Contents: Part One Stop Stressing about Stress. 1 Understanding Stress and It Can Work for You. 2 Measuring the Risk: Stress, Health, and Wellness. 3 Women and Stress: The Unique Impact of Stress on Women and How to Reduce It. 4 What is Causing You Stress. 5 What's Really Important in Your Life: Defining Your Purpose, Pasions, and Priorities. 6 What Is in Your Way: Change, Emotions, and Putting it All Together. Part Two Optimal Stress: Living in Your Beststress Zone. 7 Discovering Your BestStress Zone and Achieving the BestStress Balance. 8 Living in the BestStress Zone: Relationships, Roles, and Common Pitfalls. 9 Defending and Nurturing Your BestStress Zone: Self-Care Strategies, Relaxation, and The Power Pause. Selected References. Index.